2021
DOI: 10.1177/00469580211020187
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward Health Systems Financing in Chile

Abstract: This article presents an exploratory model to classify public attitudes towards health systems financing and organization. It comprises 5 factors (pay-as-you-use, solidarity, willingness to contribute, mixed financing, and public provision) measured by 17 indicators, selected through Exploratory Structural Equation Modeling (ESEM) applied to a sample of Chilean adults. Based on this model, cluster analysis proposed 2 groups: “Taxes-public” and “Insurance-choice,” representing 47% and 53% of interviewees, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Experience from other settings shows that determining specific revenue sources to finance the scheme, including the extent to which the scheme is financed through general taxes as opposed to contributions, can involve confrontation and disagreements between stakeholders with conflicting values and interests ( Daniels, 2007 ; Debie et al. , 2022 ), with the tensions between solidarity and freedom of choice often at the forefront ( González et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Experience from other settings shows that determining specific revenue sources to finance the scheme, including the extent to which the scheme is financed through general taxes as opposed to contributions, can involve confrontation and disagreements between stakeholders with conflicting values and interests ( Daniels, 2007 ; Debie et al. , 2022 ), with the tensions between solidarity and freedom of choice often at the forefront ( González et al. , 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Triggered by a 30 peso (about USD 0.20) rise in the cost of public transport, a sustained period of social, economic and political unrest took place during October of 2019 in Chile, known as the “Social Outburst'' or Estallido Social . Mobilization and strikes revolved mainly around deep inequalities concerning pensions, health and education [ 16 ]. However, these demonstrations quickly escalated into public disturbances, violence, repression, and serious human rights violations, bringing tension around security matters and (mis)trust in political authorities.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, a survey carried out by the Center for Conflict and Social Cohesion Studies (COES), in December 2019, asked people to assign a score from 1 to 10 regarding the importance of the different social demands, with 10 being very important. A total of 89.5% of people assigned 10 points to health [ 26 , 27 , 28 ]. Similarly, a survey carried out by the Center of Public Studies (CEP) during that same period showed that people placed “bad quality public health and education” in the fourth position when asked what they thought to be the main reason for social manifestations in Chile [ 29 ].…”
Section: Introductionmentioning
confidence: 99%